Efektivitas Penggunaan Metode Klasikal Dalam Program Tahfidz Dan Tarjim: Studi Kasus Pondok Pesantren Safinda, Banyuwangi - Fadhilah Sabrina; Akhmad Nawawi AlKhairi; Misti Hanita; Iftinani Lulu Nabila; Wahyudi Putra (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effectiveness of applying classical methods in the Al-Qur'an memorization and translation program at the Safinatul Huda Islamic Boarding School in Banyuwangi. Classical methods generally focus on collective learning in the classroom, but in the context of memorization and translation, they emphasize quantity over quality. This study aims to determine the effectiveness of the classical method in balancing both aspects. This study employs a qualitative approach with data collection techniques through in-depth interviews with students, Quran memorization teachers, and curriculum teachers. The results of the study indicate that the classical method is not only effective in increasing the quantity of memorization but also significantly contributes to understanding the meaning through the integration of translation in internalizing the values of the Quran in daily life.